Unveiling the Modernist Tapestry: Tradition and Modernity in 'A Wondering Falcon' by Jamil Ahmed - Nasir, Muhammad; Ahmad, Iesar (Pakistan Languages and Humanities Review, 2023)
The research article discusses the tension between tradition and modernity as a significant theme in literature, particularly in the late 19th and early 20th centuries. The novel ‘A Wondering Falcon’ by Jamil Ahmed is mentioned as an example of a work that explores this theme. The research aims to analyze the portrayal of tradition and modernity in the novel through a close reading and analysis of its characters, symbolism, narrative style, and social commentary. The research assumes that the novel presents a significant portrayal of the tension between tradition and modernity and that a modernist lens is useful for understanding this theme. The implications of the research are that it highlights the significance of ‘A Wondering Falcon’ within modernist literature and suggests that its exploration of tradition and modernity has broader implications for understanding societal changes and cultural shifts. By analyzing the tension between tradition and modernity in 'A Wondering Falcon,' readers can gain a deeper understanding of the complexities and challenges faced by individuals and communities in navigating the forces of tradition and modernity.